PENGARUH PENGETAHUAN DAN SIKAP TERHADAP PARTISIPASI MASYARAKAT DALAM PENGELOLAAN SAMPAH DI KAMPUNG NELAYAN UNTIA - Rahman Rahman; Mansur Sididi; Yusriani Yusriani (Jurnal Surya Muda, 2020)
Garbage is the biggest problem faced by the fishing community, which has not yet been resolved, this is because many people are still not aware of the importance of the environment so that people do not care about the problems faced, instead people throw garbage in any place. Research Objectives to analyze the influence of knowledge and attitudes on community participation in waste management in the fishing village of Untia, Makassar City. This method of research is quantitative with a cross sectional study design. The population in this study were all families in the fishing village of Untia as many as 135 families. The determination of sample size is calculated using the Slovin formula. The sampling technique is done by simple random sampling. The sample in this study was 100 households. Data collection using a questionnaire. Data analysis using the Spearman Correlation test . The results showed that the level of knowledge of waste management categorized as good was 30 (30%), for attitudes classified as low 4 (4%), for participation categorized as low 82 (82%). There is an influence of knowledge and attitudes towards community participation in waste management. It is expected that all parties, both from village officials, the government and health workers, can provide counseling, socialization regarding waste management so that community participation in waste management can increase properly